2001
DOI: 10.1046/j.1440-1789.2001.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

JC virus large T protein transforms rodent cells but is not involved in human medulloblastoma

Abstract: JC virus (JCV) together with Simian virus 40 (SV40) and BK virus (BKV), belong to the polyomavirus group and these viruses are neuro-oncogenic to rodents by expression of large T antigen (LT), which binds to cellular p53 and pRB thus reducing the anticancer potential of the cell. The function of LT has not been clarified because small t antigen (st) is transcribed from the same start codon as the overlapping reading frame of LT, and is translated as a different protein with the same N-terminal residues (1-81 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
(42 reference statements)
2
18
0
Order By: Relevance
“…These observations remain somewhat controversial, as other reports indicate that JCV is not the causative agent of these tumors (186,241,349,509). Interestingly, p53 was reported to be colocalized in the nucleus with T antigen, suggesting that the interaction of T antigen with p53 may abrogate the role of p53 in control of cell proliferation.…”
Section: Potential Association Of Jcv With Human Cancermentioning
confidence: 92%
“…These observations remain somewhat controversial, as other reports indicate that JCV is not the causative agent of these tumors (186,241,349,509). Interestingly, p53 was reported to be colocalized in the nucleus with T antigen, suggesting that the interaction of T antigen with p53 may abrogate the role of p53 in control of cell proliferation.…”
Section: Potential Association Of Jcv With Human Cancermentioning
confidence: 92%
“…However, the recent demonstration of SV40 genomes in some cancers and nonmalignant diseases in humans suggests that the virus may be etiologically meaningful in the development of those diseases [3]. Polyomaviruses JCV and BKV also have the ability to induce tumors in laboratory animals [2,18], and they have been associated with some solid tumors in humans (in particular, brain cancers) [18][19][20], although less frequently than has SV40 [1,3].…”
mentioning
confidence: 99%
“…In another European study that included 17 medulloblastomas, SV40 DNA sequences were detected in 5 (29%) specimens, BKV sequences in 1 (6%), and JCV sequences in none with PCR ampli cation and Southern methods (Huang et al, 1999). A Japanese group described negative results for JCV sequences in 8 medulloblastoma specimens; 6 by PCR ampli cation and Southern blotting, and 2 by in situ hybridization and immunostaining (Hayashi et al 2001). In contrast, North American investigators reported that 22 of 23 (96%) medulloblastomas contained JCV DNA sequences, and 5 of 23 (22%) also contained SV40 sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different groups have reported discordant results regarding the detection of SV40, JCV, and BKV DNA sequences in human medulloblastomas (Hayashi et al, 2001;Huang et al, 1999;Krynska et al, 1999;Weggen et al, 2000).…”
Section: S V40mentioning
confidence: 99%